Palmetto scale Comstockiella sabalis Comstock - Adriana Espinosa; Amanda Hodges; Greg Hodges (EDIS, 2010)
EENY465, a 3-page illustrated fact sheet by Adrianna Espinosa, Amanda Hodges, and Greg Hodges, is part of the Featured Creatures collection. It describes this scale pest of palms in southern U.S. Mexico and the Caribbean — distribution, description, life cycle, hosts, general plant damage, and management. Includes references. Published by the UF Department of Entomology and Nematology, November 2009.